700 years reconstruction of mercury and lead atmospheric deposition in the Pyrenees (NE Spain). (April 2017) - Corella, J.P.; Valero-Garcés, B.L.; Wang, F.; Martínez-Cortizas, A.; Cuevas, C.A.; Saiz-Lopez, A.
Abstract: Geochemical analyses in varved lake sediment cores (Lake Montcortès, Pre-Pyrenees) allowed reconstruction of mercury (Hg) and lead (Pb) atmospheric deposition over the past seven centuries in the Pyrenees (NE Spain). Accumulation Rates (AR) from the Middle Ages to the Industrial Period ranged from 2500 to 26130 μg m 2 .y −1 and 15–152 μg m 2 .y −1 for Pb and Hg respectively. Significant metal pollution started ca CE 1550 during a period of increased exploitation of ore resources in Spain. Colder and humid conditions in the Pyrenees during the Little Ice Age may have also favoured Hg and Pb atmospheric deposition in the lake. Therefore, the interplay between increased rainfall (wet deposition) and mining activities in the Iberian Peninsula has driven Hg and Pb AR during the Pre-industrial Period. More recently, the use of leaded gasoline in Europe in the mid-20 th century may explain the highest Pb AR between CE 1953 and 1971. The highest Hg AR occurred in CE 1940 synchronous with the highest Hg production peak in Almadén mining district (southern Spain) and the Second World War. The record of Hg enrichment in Lake Montcortès shows a decrease during the last decades in Western Europe similar to other regional records and global emission models. This study highlights the exceptional quality of varved sequences to tease apart pollutants depositional mechanisms, identify historical periods of increased atmospheric pollution and provide a historical context for pollutant baseline values to make correct assessments of recent (atmospheric) pollution in lake ecosystems. Highlights: Atmospheric Hg and Pb depositional history is reconstructed for the last 700 yrs. Atmospheric vs. run-off mercury input are detangled by microfacies analyses. Highest mercury accumulation occurred during World War II. Mercury fluxes are in agreement with those estimated by global inventories. Mining activities were the main contributors to Hg and Pb atmospheric fluxes.